2006
DOI: 10.1002/eqe.642
|View full text |Cite
|
Sign up to set email alerts
|

Shaking‐table tests on reinforced concrete frames with different isolation systems

Abstract: The effectiveness of seismic isolation in protecting structural and non-structural elements from damage has been assessed in an extensive programme of shaking-table tests, carried out on four identical 1/3.3-scale, two-dimensional, reinforced concrete (R/C) frames. Four different isolation systems were considered, namely: (i) rubber-based, (ii) steel-based, (iii) shape memory alloy (SMA)-based and (iv) hybrid, i.e. based on both SMA and steel components, isolation systems. This paper presents a comprehensive o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 104 publications
(57 citation statements)
references
References 12 publications
0
57
0
Order By: Relevance
“…4b. Referring to the typical values of design displacement (0.15-0.25 m) and period of vibration (2-3 s) of structures with SMAbased isolation systems (Dolce et al 2007), effective damping ratios ranging from 5% to approximately 27% ( ≈ 1.33 − 10) are found.…”
Section: Modeling Of Isolation Systemsmentioning
confidence: 99%
“…4b. Referring to the typical values of design displacement (0.15-0.25 m) and period of vibration (2-3 s) of structures with SMAbased isolation systems (Dolce et al 2007), effective damping ratios ranging from 5% to approximately 27% ( ≈ 1.33 − 10) are found.…”
Section: Modeling Of Isolation Systemsmentioning
confidence: 99%
“…The combination of various dissipative mechanisms is not entirely novel and the concept has 19 been widely used for base-isolation systems, where supplementary dampers are used in parallel or in series with lead-rubber-bearing (LRB) isolators [45,46]. It has been shown that the use of 21 frictional dampers (e.g.…”
Section: Afs Systems-velocity-proportional and Displacement-proportiomentioning
confidence: 99%
“…Shake table testing on energy dissipation systems includes isolation systems (Villaverde and Mosqueda, 1999;Samali et al, 2003;Dolce et al, 2007), semi-active and passive control of building structures (Sun et al, 2003;Dolce et al, 2005), and structures with viscous dampers Chang et al, 2008). Shake table testing of new types of structures and dams has also increased (Lu and Wu, 2000;Tinawi et al, 2000;Morin et al, 2002;Midorikawa et al, 2006;Wight et al, 2007;Ghaemmaghami and Ghaemian, 2008).…”
Section: Introductionmentioning
confidence: 96%